Ion microprobe–measured stable isotope evidence for ammonite habitat and life mode during early ontogeny. Issue 4 (3rd September 2018) - Linzmeier, Benjamin J.; Landman, Neil H.; Peters, Shanan E.; Kozdon, Reinhard; Kitajima, Kouki; Valley, John W.
Abstract: Ammonites have disparate adult morphologies indicative of diverse ecological niches, but ammonite hatchlings are small (~1 mm diameter), which raises questions about the similarity of egg incubation and hatchling life mode in ammonites. Modern Nautilus is sometimes used as a model organism for understanding ammonites, but despite their outward similarities, the groups are only distantly related. Trends in ammonite diversity and extinction vulnerability in the fossil record contrast starkly with those of nautilids, and embryonic shells from Late Cretaceous ammonites are two orders of magnitude smaller than nautilid embryonic shells. To investigate possible environmental changes experienced by ammonite hatchlings, we used secondary ion mass spectrometry to analyze the oxygen and carbon isotope composition of the embryonic shells and early postembryonic whorls of five juveniles of Hoploscaphites comprimus obtained from a single concretion in the Fox Hills Formation of South Dakota. Co-occurring bivalves and diagenetic calcite were also analyzed to provide a benthic baseline for comparison. The oxygen isotope ratios of embryonic shells are more like those of benthic bivalves, suggesting that ammonite eggs were laid on the bottom. Ammonite shell immediately after hatching has more negative δ 18 O, suggesting movement to more shallow water that is potentially warmer and/or fresher. After approximately one whorl of postembryonic growth, the values of δ 18 O become more positive in three of the five individuals, suggesting that these animals transitioned to a more demersal mode of life. Two other individuals transition to even lower δ 18 O values that could suggest movement to nearshore brackish water. These data suggest that ammonites, like many modern coleoids, may have spawned at different times of the year. Because scaphites were one of the short-term Cretaceous–Paleogene extinction survivors, it is possible that this characteristic allowed them to develop a broader geographic range and, consequently, a greater resistance to extinction.